Project management maturity in software development project : Klang Valley case / Hamazri Hassan Basri - Hassan Basri, Hamazri (Faculty of Computer and Mathematical Sciences, 2005)
This research presents result o f t he current 1 evel o f o rganization m aturity in s oftware development project and determines factor that contributed to the project success. The empirical approach was used to distribute and obtain the organization's current project management m aturity 1 evel. T his research mainly focuses on Klang Valley industries sector in which the software development project is categorizes as their part of the business nature. The project management maturity level and project management body of knowledge was used to determine the current maturity level of the organization. The questionnaires consist of 3 section; demographic profiles, project management maturity level and factors that contribute to the project success. Each maturity level consists of major project management characteristics, factors and process. This paper also determines the factors that contribute to the project success, ranked those factors base on the priority, level of interdependence between those factors, percentage of project success in Klang Valley and correlation between factors that contributed to the project success.